The importance of creating a successful corporate identity of MT. Kinabalu international climbathon event / Charlemagne Edward - Charlemagne Edward (Faculty of Art and Design, 2013)
Corporate identity is the image of a corporation which is designed to accord with and facilitate the attainment of business objectives. It is usually visibly manifested by way of branding and the use of trademarks (Whitbread, 2001). It includes the stationary, uniform, transportation or any items that related to corporate company. In this research the main case that the researcher focusing for is creating the successful corporate identity of Mt. Kinabalu International Climbathon Event. The summarize of each chapter can be found to the next paragraphs. Chapter one briefly described about the problem statement of the research. The problem of the research is corporate identity items is not represent the company vision and objective, in other word inconsistence corporate identity. The inconsistence of the corporate identity make audience confuse about the image of the company. In addition, many companies never noticed the importance of the corporate identity. The key of chapter two is the research objectives which; to improve people’s knowledge about the corporate identity of Mt. Kinabalu International Climbathon event; to create awareness about the importance of creating the successful corporate identity of Mt. Kinabalu international Event. The primary data collected by interview and questionnaire. In addition, 50 respondents randomly surveyed in section 7, Shah Alam to collected data. They were students and workers within the area. The secondary data taken by reference books which are The design manual by David Whitbread, Corporate Identity in Making Business, Book Design by Andrew Haslam and Graphic Art Technology by John R. K. Chapter three describe about the finding of the research methods which are interview and questionnaires. It is revealed that the importance of creating a successful corporate identity of Mt. Kinabalu International Event are, it can gets many sponsors and enhance their business. Furthermore, it can educate, motivates and asserts the belief of employees.Chapter four describe about the conclusion and the recommendation of the overall study. It explains by showing the design suggestions to overcome the currently problem of the company/event. Based on the study, corporate identify gives a big impact to spread the business and knowing widely by the audience. The good corporate identity can influence the direction of the business. The recommendation of the new items of the event such as the recommendation logo, uniform, marathon decoration and many more suggestion designs. Furthermore, this chapter discuss about the finalize result of the study.Chapter four describe about the conclusion and the recommendation of the overall study. It explains by showing the design suggestions to overcome the currently problem of the company/event. Based on the study, corporate identify gives a big impact to spread the business and knowing widely by the audience. The good corporate identity can influence the direction of the business. The recommendation of the new items of the event such as the recommendation logo, uniform, marathon decoration and many more suggestion designs. Furthermore, this chapter discuss about the finalize result of the study.Chapter four describe about the conclusion and the recommendation of the overall study. It explains by showing the design suggestions to overcome the currently problem of the company/event. Based on the study, corporate identify gives a big impact to spread the business and knowing widely by the audience. The good corporate identity can influence the direction of the business. The recommendation of the new items of the event such as the recommendation logo, uniform, marathon decoration and many more suggestion designs. Furthermore, this chapter discuss about the finalize result of the study.Chapter four describe about the conclusion and the recommendation of the overall study. It explains by showing the design suggestions to overcome the currently problem of the company/event. Based on the study, corporate identify gives a big impact to spread the business and knowing widely by the audience. The good corporate identity can influence the direction of the business. The recommendation of the new items of the event such as the recommendation logo, uniform, marathon decoration and many more suggestion designs.Furthermore, this chapter discuss about the finalize result of the study.